1990
DOI: 10.1016/0309-1651(90)90027-v
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging effect of schizandrins on active oxygen radicals

Abstract: The reactive oxygen radicals produced from human polymorphonuclear leukocytes (PMN) stimulated with PMA (phorbol myristate acetate), hydroxyl radicals generated by a Fenton reaction, and superoxide anion radicals produced by irradiating solutions of riboflavin in the presence of EDTA have been taken as the models for production of oxygen radicals. With the use of the electron spin resonance spin trapping method, the scavenging effects of schizandrol A (solA) (5 x 10(-4) M) and schizandrin B (sinB) (5 x 10(-4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Several studies have suggested that the antioxidant activities of SMS may contribute to some of its therapeutic effects (Ko et al, 2002;Wang et al, 2003;You et al, 2006). In the present study, ginsenoside Rg 2 (13.7 g/g) and schizandrin (20.5 g/g), the two abundant components found in SMS, have been shown to possess significant antioxidant activity (Zhao et al, 1990;Lu et al, 2001). These results suggested that, in addition to hepatic lipid-lowering effect, the anti-oxidative effect of SMS might reduce the depletion of hepatic GSH and reduce oxidative stress, resulting in a lower lipid peroxidation in liver.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have suggested that the antioxidant activities of SMS may contribute to some of its therapeutic effects (Ko et al, 2002;Wang et al, 2003;You et al, 2006). In the present study, ginsenoside Rg 2 (13.7 g/g) and schizandrin (20.5 g/g), the two abundant components found in SMS, have been shown to possess significant antioxidant activity (Zhao et al, 1990;Lu et al, 2001). These results suggested that, in addition to hepatic lipid-lowering effect, the anti-oxidative effect of SMS might reduce the depletion of hepatic GSH and reduce oxidative stress, resulting in a lower lipid peroxidation in liver.…”
Section: Discussionsupporting
confidence: 55%
“…It was also found that lignan compounds exerted beneficial effects on the cardiovascular system (41). Schizandrol A was an effective scavenger for oxygen radicals such as superoxide anion and hydroxyl radical (42). Schisandrin B can enhance antioxidant capacity of heart tissue by significantly increasing the activity of glutathione peroxidase, glutathione reductase, glutathione transferase, and SOD (43).…”
Section: Discussionmentioning
confidence: 99%
“…Their activity seems to be comparable to that of vitamin E, especially in liver microsomes where schisanhenol was most potent [49]. Free radical scavenging acitivity (FRSA) of schisandrol A and schisandrin B for the hydroxyl radical and superoxide anion was compared with that of vitamin E and C. Their efficiency for the hydroxyl radical was higher than that of the two vitamins, for the superoxide anion they were more potent than vitamin E [50]. According to literature FRSA against oxygen radicals is dependent on the configuration of biphenyls; Iignans with S-configuration have better activity than those with R-configuration [51].…”
Section: Biological Activities Of Lignansmentioning
confidence: 99%